Manajemen Pendidikan Anak Usia Dini di TK Bunda Wardah Kecamatan Bacukiki Barat Kota Parepare - Sri Hasnawati; Muhammad Jufri (Jurnal Multidisiplin Madani, 2022)
The background of this research is that early childhood management is very important and BUNDA WARDAH Kindergarten already has good management. Based on this background, the authors are interested in conducting research that examines the management of early childhood education in Bunda Wardah Kindergarten, West Bacukiki District, Parepare City. The formulation of the problem in this study is "how is the management of early childhood education in Bunda Wardah Kindergarten, West Bacukiki District, Parepare City?". This study aims to determine whether the process of early childhood education management in Bunda Wardah Kindergarten is in accordance with the implementation steps or not. The type of research that the author uses is phenomenological. The object of this research is the management of early childhood education. Data collection techniques in this study using interviews, observation and documentation. While the data analysis technique uses descriptive analysis techniques which include collecting data, reducing data, presenting data, and drawing conclusions.